Utilization of Remittance in Bangladesh by Migrant Families: A Micro-level Inquiry in Five Selected Upazilas (Bangladesh Journal of Public Administration, 2020)
Remittance has become a significant contributor to the Bangladesh economy. As migrant workers from Bangladesh gradually increased over the years, the amount of annual remittance to the country rose significantly. According to the World Bank, Bangladesh now stands as one of the largest recipients of remittances. The country received almost $15 billion as of June 2019 in the 2018-2019 financial year. There is a definite correlation between macro-economic policies and the flow of remittance. But both flows of remittances and their uses in Bangladesh have not been guided by any notable policy framework. Hence to maximize the flow of remittance and reap benefits from it at the domestic front, it is imperative to have a concerted policy effort. However, limited empirical works had been done about the actual productive purposes of remittance at the domestic level. This paper tries to understand the level of productive uses of remittances at the domestic level and also to find out barriers to productive uses of it. Keywords: Remittance, remittance flow, uses of remittance, barriers of productive uses, economic development, Bangladesh